Injury Prediction in Recreational Sports Using Functional Movement Screening Test - Shahrzad Zandi; Mohammad Hosein Mirzarah Kooshki; Hamideh Montazeri Taleghani (Sport Sciences and Health Research)
The aim of this study was the prediction of sport injuries in athletes participating in recreational sports with functional movement screening test (FMS). Two hundred and four athletes participating in Dodgeball, 3 on 3 basketball, 2-player volleyball and minifootball have been assessed with functional movement screening tests prior to the recreational sport Olympiad of the medical universities of Iran. Sport injuries have been recorded during the matches by research and medical team. In total, 79 athletes have endured 129 injuries during the Olympiad. The results of the logistic regression test and the Receiver operating characteristic (ROC) curve showed that the athletes with the FMS score of less than 14 are 3.63 times more vulnerable to injuries. These findings emphasize on using the FMS tests for screening athletes with high risk of injuries in recreational sports as well as the championship sports and using FMS test for predicting vulnerable athletes and organizing more targeted preventive strategy plans in recreational sports by coaches and athletes is suggested. The aim of this study was the prediction of sport injuries in athletes participating in recreational sports with functional movement screening test (FMS). Two hundred and four athletes participating in Dodgeball, 3 on 3 basketball, 2-player volleyball and minifootball have been assessed with functional movement screening tests prior to the recreational sport Olympiad of the medical universities of Iran. Sport injuries have been recorded during the matches by research and medical team.